Optical multidimensional coherent spectroscopy - Li, Hebin (Oxford: Oxford University Press, 2023)
This book provides an introduction to optical multidimensional coherent spectroscopy, a relatively new method of studying materials based on using ultrashort light pulses to perform spectroscopy. The technique has been developed and perfected over the last 25 years, resulting in multiple experimental approaches and applications to a broad array of systems ranging from atoms and molecules to solids and biological systems. Indeed, while this method is most often used by physical chemists, it is also relevant to materials of interest to physicists, which is the primary focus of this book. As well as an introduction to the method, the book also provides tutorials on the interpretation of the rather complex spectra that is broadly applicable across all subfields, and finishes with a survey of several emerging material systems and a discussion of future directions.--
Basics of ultrafast spectroscopy -- Introduction to multidimensional coherent spectroscopy -- Interpretation of multidimensional coherent spectra -- Experimental implementations -- Multidimensional coherent spectroscopy of atomic ensembles -- Frequency comb-based multi-dimensional coherent spectroscopy -- Two-dimensional spectroscopy of semiconductor quantum wells -- Three-dimensional coherent spectroscopy -- Two-dimensional spectroscopy of semiconductor quantum dots -- Two-dimensional spectroscopy of atomically thin 2D materials -- Other applications of multi-dimensional coherent spectroscopy in physics -- New trends in multidimensional coherent spectroscopy.
Includes bibliographical references (pages 245-278) and index.
Keywords: Spectrum analysis; Multidimensional spectroscopy; Optical spectroscopy; Spectroscopie optique; Spectrum analysis